Oncolytic virotherapy for metastatic breast cancer – a case report - Gesundheit, Benjamin; Muckenhuber, Alexander; Posen, Yehudit; Ellis, Ronald; Zisman, Philip David; Schmoll, Harald; Weisslein, Christine; Srinivas Raju, Jayadeepa (Frontiers in Oncology, 2023)
Background Breast cancer is one of the most common malignancies worldwide and remains incurable after metastasis, with a 3-year overall survival rate of <40%. Case presentation A 40-year-old, Caucasian patient with a grade-3 estrogen receptor-, progesterone receptor-, Her2-positive breast tumor and two lung nodules was treated with intramuscular targeted immunotherapy with trastuzumab and oral tamoxifen hormone therapy, together with customized intra-tumoral oncolytic virotherapy (IT-OV) over a 17-month period. PET/CT imaging at 3 and 6 months showed increased primary tumor size and metabolic glucose uptake in the primary tumor, axillary lymph nodes and lung nodules, which were paralleled by a hyperimmune reaction in the bones, liver, and spleen. Thereafter, there was a steady decline in both tumor size and metabolic activity until no radiographic evidence of disease was observed. The treatment regimen was well tolerated and good quality of life was maintained throughout. Conclusion Integration of IT-OV immunotherapy in standard treatment protocols presents an attractive modality for late-stage primary tumors with an abscopal effect on metastases.